PARVOVIROSE CANINA - Baldissera, Tuani Rafaela Schreiber; Baldissera, Lana Carolina Schreiber; Inkelmann, Maria Andréia (Salão do Conhecimento, 2019)
projeto de pesquisa realizado no curso de Medicina Veterinária.